PENGARUH SIFAT MACHIAVELLIAN, PERKEMBANGAN MORAL, DAN LOCUS OF CONTROL TERHADAP DYSFUNCTIONAL BEHAVIOR (Studi Empiris pada Kantor BPK dan BPKP Perwakilan Provinsi Maluku) - Tirza Oktovianti Lenggono; Senda Yunita Leatemia (Soso-Q : Jurnal Manajemen, 2019)
The purpose of this study is to examine and provide evidence of the influence of machiavellian nature, moral development, and locus of control on dysfunctional behavior both partially and simultaneously. This research is a quantitative study with several hypothesis tests. The sample was 55 BPK auditors and BPKP Maluku Province Representatives in Ambon City. The analysis tool uses multiple linear regression analysis. Primary data were obtained from questionnaire measurements with a Likert scale to test the validity and reliability of the data.The results of the study based on the validity and reliability test showed that the data was valid and reliable. Based on the t test and F test shows that the nature of Machiavellian, Moral Development, and Locus of Control influence partially and simultaneously on Dysfunctional Behavior. Variable Machiavellian Properties and Locus of Control have a positive correlation with Dysfunctional Behavior, while moral development has a negative correlation with Dysfunctional Behavior. These three variables have a strong and direct relationship and have a high percentage of dysfunctional behavior. Keywords: Machiavellian Traits, Moral Development, Locus of Control, and Dysfunctional Behavior.